PRAKTIK PENGOLAHAN DAN PEMASARAN AYAM POTONG DITINJAU DARI HUKUM ISLAM DAN HUKUM POSITIF: Studi Kasus Cahaya Broiler CV. Arvino Adjijaya di Desa Gunungsembung Kecamatan Pagaden Kabupaten Subang - Wahyu Setyo; Irvan Iswandi (Melati Institute, 2022)
This research was conducted because the researchers saw the location of this broiler chicken which made it difficult for vehicle activities to stop so the researchers wanted to know how to process and market it based on positive law and Islamic law. This study aims to explain the practice of processing and marketing broiler chicken in Cahaya Broiler (CV. Arvino Adijaya) according to Islamic law and positive law so that both consumers and producers can carry out trust in the goods being traded. This research uses qualitative research and qualitative descriptive approach. Data collection techniques were carried out in 3 ways, namely: 1) interview, 2) observation, 3) documentation. The object of this research are employees of CV. Arvino Adjijaya towards processing and marketing. Positive law and Islamic law that makes data collection. The results of this study indicate that 1) The practice of processing chicken pieces in CV. Arvino Adjijaya, Pegaden, Subang in the first stage the chickens that come are weighed, then in the second stage the chickens are separated according to the weight, the third stage the chicken is cut according to the customer's order, the fourth stage the chicken is put in the drum to be boiled, the fifth stage is cleaning the feathers , the sixth stage is the separation of chickens from their feces, after going through six stages the chickens are ready to be distributed to consumers. 2) The practice of marketing chicken pieces in CV. Arvino Adjijaya, Pegaden Subang, uses the concept of community marketing that the task of CV. Arvino Adjijaya satisfies the needs and desires of consumers and maintains the welfare of the community. There are two ways of marketing, namely, waiting for consumers to come to buy chicken which is sold based on the scales and delivering it to consumers but in large orders. 3) The practice of processing and marketing of chicken pieces in CV. Arvino Adjijaya, Pegaden Subang views Islamic law and positive law, that in the view of Islamic law, CV. Arvino Adjijaya uses the concept of buying and selling which has conditions and pillars, namely the existence of people who have al-muta'aqidain (seller and buyer), the existence of shighat (lafadz ijab and qobul), the existence of goods purchased, the exchange rate of substitute goods and the fulfillment of the terms of sale. buy. While legally positive CV. Arvino Adjijaya, has a processing and marketing operational permit which is a written legal rule that currently exists and is generally binding in the State of Indonesia.